Ozone Gas for Low Cost and Environmentally Friendly Desulfurization of Mute Grape Must - Marina Delogu; Brunella Ceccantoni; Roberto Forniti; Isabella Taglieri; Chiara Sanmartin; Fabio Mencarelli; Andrea Bellincontro (Foods, 2022)
Ozone is widely used for storage and processing facilities and food sanitization. In this research, ozone was tested as an alternative to high temperature vacuum must desulfurization in order to make a more sustainable process. Bubbling ozone in highly sulfited red must (mute must) at two treatment temperatures, a significant reduction in total and free sulfites from around 1000 mg/L to 200 and 120 mg/L at 20 and 10 °C, respectively, was observed in 24 h, but already after 4 h the concentration was halved. Air flushing of the mute must did not reduce the SO2 content. To evaluate the potential ozone effect on polyphenol oxidation, we carried out the ozone treatment on a water solution with tannins, ascorbic acid, or potassium metabisulfite (MBK) as single and as mixture. In 1 h, 2/3 of sulfite disappeared with the treatment, but the reduction was greater with ascorbate and tannins; the same was observed for ascorbate, whereas tannins decreased to a lesser extent when combined with ascorbate and MBK. Taken together, the results indicate that ozone could be an environmentally friendly, low cost, treatment for desulfurization, especially for white must, and is also easy to use by small wineries.